Path analysis of morphological traits influencing performance in Cicer arietinum genotypes under semi-arid conditions - Sabaghnia, Naser; Janmohammadi, Mohsen (Acta Biologica Szegediensis, 2025)
Identification of the most desirable genotypes and determining the correlation of different traits with seed yield performance, as well as understanding their cause and effect, provides plant breeders with the ability to select the most appropriate and logical combination of yield components that lead to higher economic performance. In order to identify yield components of chickpea, 50 genotypes were investigated in Gavshaleh, Saqqez, Iran (36°19′54″N and 47°19′07″E). Statistical analysis included simple correlation coefficients of traits, multiple stepwise regression, and path analysis. The traits measured included days to flower initiation (DF), canopy width (CW), days to maturity (DM), the first pod height from the ground (FPH), chlorophyll content (CHL), plant height (PH), number of subsidiary branches (SB), number of pods per plant (NPP), pod weight (PW), shuck weight per plant (SW), plant dry weight (PDW), number of seeds per pod (SP), hundred-seed weight (HSW), protein percentage (PP), and seed yield (SY). The results of simple correlations demonstrated positive significant association of seed yield with SB, SP, and NPP, while it was negatively associated with DF, DM, and PW. Path analysis revealed the primary-order roles of SP and HSW in determining SY, with SP having a larger direct effect (1.04) compared to HSW (0.25). Estimation of direct effects via bootstrapping indicated reliable results with low amounts of standard error and bias. Additionally, the number of subsidiary branches had the most significant indirectly impact on seed yield performance via the pods’ number per plant. Therefore, it is recommended that these two traits be prioritized in breeding programs aimed at increasing seed yield. Finally, SP, HSW, NPP, and SB can be beneficially utilized for selection in genetic improvement projects targeting chickpea yield enhancement.